2020
DOI: 10.22271/chemi.2020.v8.i2n.8884
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of natural products and fungicides against powdery mildew of ber

Abstract: Indian jujube or ber (Ziziphus mauritiana Lamk.) is one of the most common fruit, indigenous to an area joined from India to China. Powdery mildew of ber incited by Oidium erysiphoides f. sp. ziziphi, Yan and Wang is the most important disease that causes maximum reduction in yield and quality of ber fruits. Exclusive reliance on fungicides for the control of disease of various crops resulted in residue and environmental hazards. Therefore, in recent years, efforts are being diverted to employ higher plants, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…They also reported that among non-systemic fungicides; iprodione + carbendazim (58.39%) recorded notably highest inhibition followed by Mancozeb (45.34%). Similarly, findings of Choudhary et al (2020); Kumar et al (2011) and Zaine (2011) also support our results. They all proposed hexaconazole as best fungicide against various fungal diseases.…”
Section: Discussionsupporting
confidence: 91%
“…They also reported that among non-systemic fungicides; iprodione + carbendazim (58.39%) recorded notably highest inhibition followed by Mancozeb (45.34%). Similarly, findings of Choudhary et al (2020); Kumar et al (2011) and Zaine (2011) also support our results. They all proposed hexaconazole as best fungicide against various fungal diseases.…”
Section: Discussionsupporting
confidence: 91%
“…week. Several workers recorded similar observations with powdery mildew of different crops as neem oil and NSKE on Abelmoschus esculentus (Raghupathi et al, 1997), sunflower oil on tomato (Ko et al, 2003), citronella oil and neem oil on Nephelium lappaceum (Alahakoon et al, 2010), neem oil on okra (Moharamand Ali, 2012) and garlic extract and neem oil on ber (Choudhary et al, 2020).…”
Section: Resultsmentioning
confidence: 74%
“…However, a recent bibliography (2020-2022) published after the last extension of use, triggered new possible requests for strawberries (Nam et al, 2005), ber (Ziziphus mauritiana Lamk.) (Choudhary et al, 2020) and apple (Cromwell, 2009) protection against cryptogamic diseases. Current results exhibited in Figure 1 confirm interesting activity and efficacy of cow milk of cucumber protection giving rise to yield increase.…”
Section: Cow Milkmentioning
confidence: 99%